In propositional logic we had studied the following rules:

(P • Q)   ->  P, Q   
~(P ∨ Q)  ->  ~P, ~Q   
~(P ⊃ Q)  -> P, ~Q  

and say, the inference rules:

~(P • Q), P -> ~Q
(P ∨ Q), ~P -> Q
(P ⊃ Q), ~Q -> ~P

Now in predicate logic you can use these rules but my question is how do I decide where does the negation go? This is unfortunately not clearly stated in the book.

For example:

If I have:

~((x)Pa ⊃ (x)Qa)

I can deduce two inferences from this such as firstly:


But for the second inference where does the negation go?

Is it (x)~Qa or ~(x)Qa ?


¬(P → Q) is equivalent to : P ∧ ¬Q.

Thus, ¬((x)Px → (x)Qx) must be : (x)Px ∧ ¬(x)Qx.

  • Is it true in all the cases that the negation always goes before the quantifier? I am confused about where does the negation of this (x)~Qa comes from if the negation of (x)(Qx) is ~(x)Qx?
    – cpx
    Oct 9 '15 at 11:29
  • @cpx - It depends on what your are expressing : "not all men are Greeks" is ¬(x)Qx (that is true) and it is different from "all men are not-Greeks", i.e. (x)¬Qx (that is false). Oct 9 '15 at 11:35
  • I see. So, I guess that particular case is not actually a negation of something but rather an expression itself. In other words, all the negations should go in the front of quantifier if it is of something else, right?
    – cpx
    Oct 9 '15 at 11:41
  • @cpx - YES; the negation of an expression A is always ¬A. Then, there are "equivalences", like those between ¬(x)Qx and (∃x)¬Qx and between (x)¬Qx and ¬(∃x)Qx. Oct 9 '15 at 12:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.